HUBUNGAN ANTARA GRIT DAN REGULASI DIRI PADA MAHASISWA YANG SEDANG MENYUSUN SKRIPSI - Yenita Yenita; Monika Monika (Fakultas Psikologi Universitas Tarumanagara, 2026)
University student, particularly those working on their final projects, often navigate a range of academic demands that can trigger stress, anxiety, and even procrastination, making self-regulation a crucial skill for managing the thesis-writing process in a steady and effective manner. In this context, grit—defined as long-term perseverance toward meaningful goals—plays an important role in sustaining effort, remaining committed, and staying resilient when students encounter academic or emotional obstacles. These two constructs are assumed to be related, as students with higher levels of grit are generally better at managing their behaviors, emotions, and thoughts while completing their thesis. To examine this assumption, the present study employed a quantitative correlational design involving 215 final-year students aged 19–25. The instruments used were the Short Grit Scale developed by Duckworth et al. (2007) and the Self-Regulation Questionnaire designed by Brown, Miller, and Lawendowski in Carey et al. (2004). Data were analyzed using Spearman’s correlation due to the non-normal distribution of the variables. The results revealed a positive and significant relationship between grit and self-regulation (r = 0.552, p < 0.000), indicating that students with higher grit tend to show stronger self-regulatory abilities throughout the thesis process. These findings highlight that both grit and self-regulation are essential components supporting academic persistence and the successful completion of final-year academic tasks.